Prime ideals in noncommutative Iwasawa algebras - Ardakov, K (2006)
We study the prime ideal structure of the Iwasawa algebra ΛG of an almost simple compact p-adic Lie group G. When the Lie algebra of G contains a copy of the two-dimensional non-abelian Lie algebra, we show that the prime ideal structure of ΛG is somewhat restricted. We also provide a potential example of a prime c-ideal of ΛG in the case when the Lie algebra of G is s-fraktur sign l-fraktur sign2(ℚp). © 2006 Cambridge Philosophical Society.